Psychoeducation to Improve Learning Motivation at SDN X Surakarta: Psikoedukasi Untuk Meningkatkan Motivasi Belajar di SDN X Surakarta - Arsita, Dina; Fathia Fitri Azahra; Kusuma Arum Dyana Kumara; Usmi Karyani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Low learning motivation among elementary school students remains one of the major challenges in education, as it directly affects academic achievement, discipline, and character development. This issue is often reflected in students’ lack of focus, initiative, and active participation during learning activities. Such conditions require interventions that address not only cognitive but also affective and psychological aspects to foster intrinsic motivation. This community service program aimed to enhance students’ learning motivation at SDN X Surakarta through a psychoeducation intervention. The method consisted of four stages: problem identification, intervention design, implementation, and evaluation. Psychoeducation was chosen because it integrates educational and psychological principles through interactive activities that promote self-awareness, responsibility, and intrinsic motivation. The program was implemented on May 10, 2025, involving 36 students from grades 1 to 5. The 45-minute session included an opening, ice breaking, pre-test, delivery of psychoeducational material on the importance of learning, inspirational video viewing, interactive games, post-test, reward distribution, and closing. The effectiveness of the intervention was measured using pretest and posttest assessments based on the presented material to evaluate changes in students’ understanding of learning motivation. The results showed an increase in the average motivation score from 4.667 to 4.917 (p = 0.032), indicating a significant improvement after the intervention. These findings highlight the effectiveness of psychoeducation as a strategy to improve learning motivation among elementary students. More broadly, this program provides valuable implications for schools to integrate psychoeducational activities into learning policies and character development practices to create a more supportive, participatory, and psychologically empowering learning environment.